2018
DOI: 10.3791/56606
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Immunofluorescence Analysis and Quantification of Intratumoral PD-1<sup>+</sup> Tim-3<sup>+</sup> CD8<sup>+</sup> T Cells

Abstract: Immune cells are important components of the tumor microenvironment and influence tumor growth and evolution at all stages of carcinogenesis. Notably, it is now well established that the immune infiltrate in human tumors can correlate with prognosis and response to therapy. The analysis of the immune infiltrate in the tumor microenvironment has become a major challenge for the classification of patients and the response to treatment. The co-expression of inhibitory receptors such as Program Cell Death Protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…The 45 renal biopsies were analyzed using the software inForm Tissue Finder 2.3.0 (PerkinElmer). Only scanned images at ×20 (ROI fields) were analyzed by inForm . This software is based on a supervised machine‐learning algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…The 45 renal biopsies were analyzed using the software inForm Tissue Finder 2.3.0 (PerkinElmer). Only scanned images at ×20 (ROI fields) were analyzed by inForm . This software is based on a supervised machine‐learning algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…These findings indicate that infiltrated Tim‐3 + PD1 + CD8 + T cells are potential mediators to create an aggressive phenotype in patients with RCC 110 . It was also reported that co‐expression of Tim‐3 and PD‐1 on tumour‐infiltrating CD8 + T cells was associated with a poor prognosis in RCC patients 111 . CD4 + and CD8 + T cells of TIL in renal cell carcinoma patients have higher frequencies of Tim‐3 + , PD‐1 + and LAG‐3 + antigens 112 .…”
Section: Importance Of Tim‐3 Expression In Rccmentioning
confidence: 56%
“…Our data point to a favorable outcome for MSS‐ImmEx hi tumors that have high proportions of Tim‐3 + PD‐1 + CD8 + TILs. This is in contrast to renal cell carcinoma, where high proportions of such cells are associated with poor prognosis [41,42]. Furthermore, CD8 + T cells expressing PD‐1 but not Tim‐3 correlated with higher progression‐free survival and objective response rates to anti‐PD‐1 therapy in renal cell cancer [43].…”
Section: Discussionmentioning
confidence: 99%